Domestication and Captive Breeding Efforts of the Endangered Endemic Betta (Betta rubra) from Sumatra as a Potential Ornamental Fish - Jati, Ciptaning Weargo; Noor, Huriyatul Fitriyah; Fathurrohman, Aulia (Jurnal Biologi Tropis, 2026)
This study assessed early domestication and captive breeding of the endangered endemic Betta (Betta rubra) from Sumatra. The experiment ran for six weeks (July–August 2025) at Jatimas Fish Farm Laboratory, Lampung, using broodstock collected from peat swamps in Batanghari, Jambi. Of 15 pairs, six spawned successfully and produced an average of 35.8 ± 4.3 larvae per spawn. Larvae were reared for ten days on different starter feeds (Tubifex, Artemia, Moina); the highest survival was achieved on chopped Tubifex (100%). Because B. rubra is a paternal mouthbrooder (eggs incubated inside the male’s mouth), direct counting of initial eggs without invasive procedures was impractical; therefore, we report larvae produced as the primary reproductive metric. Findings indicate that early domestication of B. rubra is feasible under controlled conditions and that chopped Tubifex is an effective starter feed for larval rearing.